Examination of the effects of population age distribution and oil rent on inequality of income: dynamic panel for selected oil-exporters MENA countries - Hossein Amiri; Masoud Yahoo; Mohammad Hossein Karim (Penerbit Universiti Kebangsaan Malaysia, 2025)
This paper analyzes the impacts of oil rents and population age structure on inequality in income for selected oil-exporters MENA countries. The research model is estimated using Generalized Method of Moments (GMM) for dynamic panel for the period 2006–2020. Results indicate that the distribution of income in these nations has been significantly affected by the oil rents. Additionally, a rise in the dependency ratio and the population over 65 and in the 0–14 age group both significantly and negatively affect the distribution of income. However, increasing the working-age population to total population ratio improves income distribution. Oil price fluctuations and related uncertainties changes economic structure of countries in MENA region over the past decade. Several of these countries have worked to diversify their economies and enhance welfare and income distribution in recent years. Along with reducing income inequality attempts, different policies taking into account of different variables have been suggested to decrease inequality in income. Therefore, identifying the extends and direction of changes in income distribution and its attributes is a major challenging issue facing policy makers. Policymakers should reduce income inequality by providing adequate childcare and family benefits to reduce dependency ratio, investing in education, increasing per capita income, properly managing and utilizing total natural resource rents % of GDP, design and implement free trade agreements, and plan to mitigate the effects of ageing.